Role of hyaluronate containing artificial tears in mitigating markers of dry eye disease using in vitro models - Sharel P Karkada; Sheril P Karkada; Anushree Bhatkal; Srihari Balaraj; Ritica Mukherji; Arkasubhra Ghosh; Pooja Khamar; Nimisha R Kumar (Indian Journal of Ophthalmology, 2025)
Purpose: Ocular surface discomfort and dry eye disease (DED) are the most common conditions addressed by ophthalmologists worldwide. Artificial tear substitutes are used as the first line of treatment management for DED patients. The present study was performed to understand the role of artificial tear formulation namely Soha Liquigel (0.18% sodium hyaluronate with trehalose) and Soha (0.1% sodium hyaluronate) for the treatment of DED in vitro. Human corneal epithelial (HCE) cells were used in adapted cell culture conditions which induce relevant cellular and molecular modifications thus mimicking the DED. Methods: Artificial tears containing either sodium hyaluronate (SH) (Soha 0.1%, Sun Pharma) or a combination of SH with trehalose (Soha Liquigel 0.18%, Sun Pharma) were compared with respective controls to analyze the effect on desiccation-induced stress or oxidative stress or hyperosmolarity induced stress on HCE cells. Cellular viability was evaluated using the trypan blue assay, while epithelial morphology was observed under light microscopy. Real-time polymerase chain reaction (RT-PCR) was utilized to analyze the transcriptional profile of a specific set of gene signatures, namely S100A7, FOS, SOD-2, COX2, TonEBP, IL6, MCP1, and IL10. Results: The response of HCE cells to desiccation stress (24 hr) was observed through alterations in their cellular morphology, which were subsequently restored by applying Soha Liquigel. Oxidative stress was induced using 100 nM of H2O2 on HCE cells (short- 24 h and long-term 5 days) and measured using increased expression of S100A7, an oxidative stress-responsive gene. Oxidative-stressed HCE cells after treatment with Soha Liquigel showed reduced pro-oxidant gene and COX2 expression and elevated anti-oxidant genes, FOS, and SOD levels. HCE cells were subjected to +100mOsmol and +200mOsmol NaCl-containing media, inducing hyperosmolar stress that imitates the symptoms of DED. Further, these hyperosmolar stressed cells were treated with Soha Liquigel and Soha eye drops for 24 h and 5 days. Both eye drops rescued the cell morphology under hyperosmolar conditions in both short- and long-term treatments. Increased TonEBP levels confirm the osmotic stress in HCE cells. Reduction in IL6, MCP1, TonEBP, and elevated expression of IL10 in hyperosmotic stressed HCE cells treated with either of the artificial tears indicates their osmo-protection properties. Conclusion: By using desiccation, oxidative, and hyperosmolar stress simulated in HCE cells in culture, we observed that SH-containing artificial tears provided bio-protection, osmo-protection, and anti-oxidant benefits that were further strengthened with SH and trehalose combination.